Management of multiple trauma with mainly thoracic and abdominal injuries： a report of 1166 cases - 杨俊 高劲谋 胡平 李昌华 赵山宏 林曦 (Chinese journal of traumatology, 2009)
Objective： To discuss the diagnosis and treatment of multiple trauma with mainly thoracic and abdominal injuries. Methods： A retrospective analysis was performed on data of multiple trauma cases with mainly thoracic and/or abdominal injuries. Results： Of 1166 cases, 72.3% were found with shock. The operation rates of thoracic and abdominal injuries were 14.8% （119/804） and 83.5% （710/850） respectively （ x^2=780.683, P 〈0.01）. The operation rates of blunt and penetrating thoracic injuries was 6.8% （42/617） and 40.6% （76/187） respectively （ x^2=131.701, P〈0.01）. The operation rates of blunt and penetrating abdominal injuries were 77.1% （434/563） and 96.1% （276/287） respectively （ x^2=50.302, P〈0.01）. The operation rates of blunt thoracio-abdominal injuries were 6.8% （42/617） in thoracic region and 77.1% （434/563） in abdomen respectively （x^2=544.043, P〈0.01 ）. Among the cases of abdominal injuries, 41 received arteriography embolism, with the efficacy of 95.1% （39/41）. Total mortality rate was 6.1%. The mortality rates of blunt and penetrating injuries were 7.3% （62/854） and 2.9% （9/312） （ x^2=6.51, P〈0.005）. The deaths were mainly due to large volume of blood loss. Conclusions： When both thoracic and abdominal injuries exist, laparotomy is frequently required rather than thoracotomy. Laparotomy is seldomly used for blunt thoracic injuries, but usually used for penetrating thoracic and abdominal injuries. Mortality rate of penetrating thoracic and abdominal injuries is markedly lower than that of blunt injuries. Surgical operation is still important for those patients with penetrating thoracic or abdominal injuries.